Improving Health Service Delivery in Developing Countries: From Evidence to Action - Peters, D.H; El-Saharty, S.; Siadat, B.; Janovsky, K; Vujicic, M (The World Bank, 2013)
Reliable information on how health service strategies affect the poor is in short supply. In an attempt to redress the imbalance, Improving Health Service Delivery in Developing Countries presents evidence on strategies for strengthening health service delivery, based on systematic reviews of the literature, quantitative and qualitative analyses of existing data, and seven country case studies. The authors also explore how changes in coverage of different health services affect each other on the national level. Finally, the authors explain why setting international targets for health services has been not been successful and offer an alternative approach based on a specific country’s experience.The book’s findings are clear and hopeful: There are many ways to improve health services. Measuring change and using information to guide decisions and inform stakeholders are critically important for successful implementation. Asking difficult questions, using information intelligently, and involving key stakeholders and institutions are central to the “learning and doing” practices that underlie successful health service delivery.
Keywords: Public health; Health care; Deliver; Health services; Development projects; Evaluation; Afghanistan; Ethiopia; Ghana; Rwanda; Uganda; Vietnam; Zambia